Influência dos óleos essenciais de Cinnamomum cassia e Cymbopogon flexuosus sobre a suscetibilidade e fatores de virulência em leveduras do complexo Cryptococcus neoformans - Oliveira, Lucas Daniel Quinteiro de (2017)
The Cryptococcus neoformans complex comprises two species responsible for causing cryptococcosis, the main manifestation being meningoencephalitis in immunocompromised hosts. Its pathogenicity is related to virulence factors. The treatment of this disease is difficult because the drugs present high toxicity, resistance of the fungus and little therapeutic efficiency. Research with biologically active natural products has shown that essential oils (OEs) have important antifungal activity. Thus, the present study had as objective to evaluate the antifungal efficacy and action on the virulence factors in C. neoformans complexes of OEs of Cinamomum cassia (Cinnamon of China) and Cybopogom flexuosus (Lemon Grass). By means of the microdilution technique in broth, OEs had MIC ranging from 8 to 256 μg / ml and CFM from 16 to 512 μg / ml. C. cassia promoted a 47.8% reduction in capsule size and inhibited melanin synthesis in 30% of the isolates. The evaluation of this OE on the activity of exoenzymes phospholipase, urease and DNAse demonstrated inhibition in 15%, 30% and 25% of the evaluated isolates respectively. C. flexuosus reduced the size of the capsule by 48.7%, inhibited the production of melanin, urease, phospholipase and DNAse by 30%, 30%, 25% and 15% respectively. The data demonstrated that the isolates did not produce proteinase and the hemolytic activity was reduced by 15% for C. cassia and 45% C. flexuous. The results highlight the potential of these OEs in the treatment of cryptococcosis as well as the inhibition of virulence factors. These data are promising, and further research is needed to develop of a new drug.